PAPD5/7 Are Host Factors That Are Required for Hepatitis B Virus RNA Stabilization. Issue 4 (1st March 2019) - Mueller, Henrik; Lopez, Anaïs; Tropberger, Philipp; Wildum, Steffen; Schmaler, Josephine; Pedersen, Lykke; Han, Xingchun; Wang, Yongguang; Ottosen, Søren; Yang, Song; Young, John A.T.; Javanbakht, Hassan
Abstract : RG7834 is a potent, orally bioavailable small‐molecule inhibitor of hepatitis B virus (HBV) gene expression that belongs to the dihydroquinolizinone (DHQ) chemical class and uniquely blocks production of both viral DNA and antigens. In this study, we used DHQ compounds as tools in a compound‐based adaptation version of the yeast three‐hybrid screen to identify the cognate cellular protein targets, the non‐canonical poly(A) RNA polymerase associated domain containing proteins 5 and 7 (PAPD5 and PAPD7). Interaction with RG7834 was mapped to the catalytic domains of the two cellular enzymes. The role of PAPD5 and PAPD7 in HBV replication was confirmed by oligonucleotide‐mediated knockdown studies that phenocopied the result seen with RG7834‐treated HBV‐infected hepatocytes. The greatest effect on HBV gene expression was seen when PAPD5 and PAPD7 mRNAs were simultaneously knocked down, suggesting that the two cellular proteins play a redundant role in maintaining HBV mRNA levels. In addition, as seen previously with RG7834 treatment, PAPD5 and PAPD7 knockdown led to destabilization and degradation of HBV mRNA without impacting production of viral RNA transcripts. Conclusion : We identify PAPD5 and PAPD7 as cellular host factors required for HBV RNA stabilization and as therapeutic targets for the HBV cure.